Prevalence of Oral Manifestations and Their Association with CD4/CD8 Ratio and HIV Viral Load in South India - Sharma Gaurav; Pai M. Keerthilatha; Nagpal Archna (International Journal of Dentistry)
The objective of the present research was to determine the prevalence of oral manifestations in an HIV infected population from south India and evaluate their association with HIV viral load and CD4/CD8 ratio. Intraoral examination of 103 patients, whose CD4/CD8 ratio was available, were conducted. HIV viral loads were available for thirty patients only. The prevalence of oral manifestations was 80.6% (83/103). The most common oromucosal lesion was erythematous candidiasis (EC) (38.8%) followed by melanotic hyperpigmentation (35.9%). Patients having any oral manifestation had a mean CD4/CD8 ratio of 0.24. EC had positive predictive value of 85.0% for CD4/CD8 ratio <0.30. The prevalence of oral manifestations in patients taking ART was lesser (78.6%) as compared to patients not taking ART (82%). Patients having any oral manifestation had a higher HIV viral load as compared to patients not having any oral manifestations (𝑃<0.05). Pseudomembranous candidiasis (PC) was significantly associated with higher HIV viral loads (>20,000 copies/mL) (𝑃<0.05). Patients having EC had 4 times greater chance of having CD4/CD8 ratio <0.30. PC can be considered as a marker of immune suppression (HIV viral load >20,000 copies/mL).